Bureaucratic Ethics in Enhancing Public Trust in Social Assistamce Services: A Case Study of Bululi Village, Asparaga District - Malik, Nuralisa; Kamuli, Sukarman; Agussalim, Alfiyah (Public Policy Journal, 2025)
This study analyzes the role of bureaucratic ethics in strengthening public trust in government social assistance services at the Bululi Village Office, Asparaga District, Gorontalo Regency. The problems arise due to unequal treatment, lack of fairness in the distribution of social assistance, and low accountability of village officials. Using a qualitative descriptive method, data were collected through observation, interviews, and documentation involving both village apparatus and community members. The analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that: (1) Equality in service delivery remains limited, with preferential treatment for certain groups; (2) Equity in distributing social assistance is often compromised by bias and lack of transparency; (3) Loyalty of officials to institutional values and regulations is challenged by external pressure and informal practices; and (4) Responsibility has been implemented relatively well, although weaknesses remain in discipline and consistency. The study concludes that strengthening bureaucratic ethics—particularly in fairness, accountability, and discipline—is crucial to restoring and maintaining public trust. These findings contribute to the discourse on good governance at the local level and highlight the urgency of ethical reforms in village administration.